A concept dual-motor powertrain for battery electric vehicles: Principle, modeling and mode-shift. (July 2023) - Tian, Yang; Wang, Zihao; Ji, Xiaoyu; Ma, Lei; Zhang, Lipeng; Hong, Xianqian; Zhang, Nong
Abstract: Integration of dual-motor powertrains in battery electric vehicles (BEVs) provides significant opportunities for promoting energy saving and dynamic performance improvement. This paper proposes a novel dual-motor powertrain (DMP), mainly including a brake and a Simpson planetary gearset (SPG). This SPGDMP features four work modes, two single-motor modes and dual-motor torque and speed modes. Furthermore, a quality mode-shift process can be achieved by simultaneously or respectively regulating two motors and the brake. Firstly, to capture the transient behaviors of SPGDMP, the detailed and original dynamic model is established. Afterwards, the longitude vehicle jerk is determined as the major index to evaluate the mode-shift quality. Then, the mechanism of realizing the minimum jerk is systematically revealed, i.e. seamless output torque transmitting during the mode-shift. After that, a model-based mode-shift strategy is specifically proposed to ensure output torque seamlessly when triggering mode-shift. Finally, a series of results demonstrate that the SPGDMP is capable of carrying out four independent working modes and guaranteeing vehicle ride comfort via the proposed superior strategy. Highlights: Proposing a novel dual-motor powertrain for battery electric vehicles. Building the detailed and original dynamic model of this powertrain. Revealing the mechanism of the seamless mode-shift by dynamics analysis. Validating the effectiveness of the proposed seamless mode-shift strategy.